Curcumin induces endoplasmic reticulum stress-associated apoptosis in human papillary thyroid carcinoma BCPAP cells via disruption of intracellular calcium homeostasis. Issue 24 (June 2018) - Zhang, Li; Cheng, Xian; Xu, Shichen; Bao, Jiandong; Yu, Huixin
Abstract: Background: Thyroid cancer is the most common endocrine tumor. Our previous studies have demonstrated that curcumin can induce apoptosis in human papillary thyroid carcinoma BCPAP cells. However, the underlined mechanism has not been clearly elucidated. Endoplasmic reticulum (ER) is a major organelle for synthesis, maturation, and folding proteins as well as a large store for Ca 2+ . Overcoming chronically activated ER stress by triggering pro-apoptotic pathways of the unfolded protein response (UPR) is a novel strategy for cancer therapeutics. Our study aimed to uncover the ER stress pathway involved in the apoptosis caused by curcumin. Methods: BCPAP cells were treated with different doses of curcumin (12.5–50 μM). Annexin V/PI double staining was used to determine cell apoptosis. Rhod-2/AM calcium fluorescence probe assay was performed to measure the calcium level of endoplasmic reticulum. Western blot was used to examine the expression of ER stress marker C/EBP homologous protein 10 (CHOP) and glucose-regulated protein 78 (GRP78). X-box binding protein1 (XBP-1) spliced form was examined by reverse transcriptase-polymerase chain reaction (RT-PCR). Results: Curcumin significantly inhibited anchorage-independent cell growth and induced apoptosis in BCPAP cells. Curcumin induced ER stress and UPR responses in a dose- and time-dependent manner, and the chemical chaperone 4-phenylbutyrate (4-PBA) partially reversed the antigrowth activity of curcumin. Moreover, curcumin significantly increased inositol-requiring enzyme 1α (IRE1α) phosphorylation and XBP-1 mRNA splicing to induce a subsets of ER chaperones. Increased cleavage of activating transcription factor 6 (ATF6), which enhances expression of its downstream target CHOP was also observed. Furthermore, curcumin induced intracellular Ca 2+ influx through inhibition of the sarco-endoplasmic reticulum ATPase 2A (SERCA2) pump. The increased cytosolic Ca 2+ then bound to calmodulin to activate calcium/calmodulin-dependent protein kinase II (CaMKII) signaling, leading to mitochondrial apoptosis pathway activation. Ca 2+ chelator BAPTA partially reversed curcumin-induced ER stress and growth suppression, confirming the possible involvement of calcium homeostasis disruption in this response. Conclusions: Curcumin inhibits thyroid cancer cell growth, at least partially, through ER stress-associated apoptosis. Our observations provoked that ER stress activation may be a promising therapeutic target for thyroid cancer treatment. Figure. No caption available.